Strategi Meningkatkan Keakuratan Hasil Terjemahan Bahasa Indonesia ke Bahasa Inggris Menggunakan Google Translate - Jubaidah, Siti; Aliurridha (CV Insan Kreasi Media, 2024)
This study aims to find ways or strategies that can be used to get much more accurate Google Translate translation results, especially translations from Indonesian to English. This study uses qualitative research methods because it is carried out to provide an explanation of a phenomenon which will later build a theory related to this phenomenon. This study can be categorized as an experimental research study; because it uses two research objects and then compares the results. The two objects are Chapter 1 of the novel Laskar Pelangi by Andrea Hirata which was directly translated using Google Translate and Chapter 1 of the novel Laskar Pelangi by Andrea Hirata which underwent adjustments (in the form of strategy implementation) before being translated using Google Translate. These two translations were then compared to see which version was most similar to the translation of professional translator Angie Killbane who had translated the novel into English. This study only focuses on the similarity of Google Translate translation results for texts that have not undergone adjustments and Google Translate translation results for texts that have undergone adjustments with the translation results of professional translators. The results of this study found that text translations that underwent adjustments were more similar to the results of translations by professional translators. The adjustment in question is to clarify the meaning of the sentence by adding time information and adapting the language so that Google Translate can understand the meaning of the sentence correctly so that it can produce a translation that is much more accurate, acceptable and reasonable, in accordance with translation rules.